Application of network traffic flow model to road maintenance - Yang, Chao; Remenyte-Prescott, Rasa; Andrews, John (Thomas Telford, 2015)
The study shows how the evolution of two-way traffic flows on a local highway network can be predicted over time using a network-level traffic flow model (NTFM) to model both urban and motorway road networks. After a brief review of the main principles of the NTFM and its associated sub-models, the paper describes how a maintenance worksite can be modelled using a roadwork-node sub-model and a network solution routine in the NTFM. In order to model the two-way traffic flow in the road network, an iterative simulation method is used to generate the evolution of dependent traffic flows and queues. The NTFM has been applied to model the traffic characteristics and the effects of maintenance activities on the local Loughborough–Nottingham highway network. The study has demonstrated that the methodology is useful in selecting various worksite arrangements in order to reduce the effects of maintenance on road users.